L'ostinato, procédé musical universel - Schnapper, Laure (Paris Champion, 1998)
A constitutive principle of music considered almost universal, the ostinato can be found in both Western art music and virtually all popular musical traditions. Drawing on a broad corpus, this approach highlights similarities in the use of ostinato in music that otherwise have nothing in common. (Translated with Deepl.com)
Includes bibliographical references (p. [253]-263) and index.
Keywords: Basso ostinato